CREC7‘s infrastructural investment in the DRC : an in-depth study of the motives for Chinese outward FDI - Van Der Lugt, Sanne (Stellenbosch : Stellenbosch University, 2011)
Thesis (MA)--Stellenbosch University, 2011.